Hubungan Tingkat Pengetahuan Terhadap Keberhasilan Pengobatan Tuberkulosis di Puskesmas Kecamatan Johar Baru Jakarta Pusat Tahun 2016 - Utami, Nurul Amalia; Tunru, Insan Sosiawan A; Yusnita, Yusnita (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2018)
Tuberculosis (TB) is a contagious disease caused by the group of Mycobacterium bacteria, Mycobacterium tuberculosis. There are six countries with the highest number of TB incidents in the world, including Indonesia with a prevalence of 1,020 per 100,000 inhabitants located second after India. Based on the results of monitoring and evaluation of Tuberculosis External Monitoring Mission Team in 2008, the success of treatment is still low. Many factors that influence the success of tuberculosis treatment one of them is the level of knowledge. This study aims to see and prove whether there is a relationship of knowledge level to the success of treatment in patients with tuberculosis and done cross-sectional. The result of the research shows that there are 45 respondents (80,4%) and the knowledge level of the respondent has good knowledge, 22 people (39,3%) from 56 samples. From the results of statistical tests using Chi-Square test obtained P value> 0.05 is 0.069.